Evaluation of Some Heavy Metal Contamination in Agricultural Soils at Malleri, Kwami L.G.A. Gombe State, Nigeria - Babangida, Hammani; Ibrahim, Abubakar; Danladi, Audu; Mustapha, Abdulkadir; Zaliha, Muhammad; D. Kwairanga, Mohammed (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2024)
The study evaluates the presence of heavy metals contamination in agricultural soils in Malleri, Kwami Local Government Area, Gombe State, Nigeria. Thirty two (32) soil samples were taken randomly from six distinct farms using a soil auger and labeled at depths ranging from 0 to 25 cm. The results for Arsenic (As), Lead (Pb), Cadmium (Cd), Chromium (Cr), Iron (Fe), Copper (Cu), and Cobalt (Co) in the agricultural soils of Malleri, Kwami Local Government Area of Gombe State, Nigeria, showed a significant difference (p<0.05). The following is the decreasing order of heavy metals: Ni > Fe > Cu > Cr > As > Cd > Pb. The reason for this difference may be ascribed to the low agricultural practices such as fertilizer application, intense use of manure and the sandy nature of the soil. These factors can have potentials to cause metals to seep into lower ground layers. The study’s conclusions led to the following recommendations being made: farmers should use organic manures and biofertilizers in place of chemical pesticides and fertilizers. By using natural techniques of pest control instead of pesticides, soil contamination can be reduced and food safety can be increased. Food crops should be properly cleaned to remove as much soil as possible from soils with elevated heavy metal concentrations in order to decrease health concerns .